Numerical Modeling of GFRP Reinforced Concrete Slabs - Omer R EL Zaroug, John P Forth, Jianqiao YE (Journal of engineering sciences and information technology, 2017)
The use of non-metallic fibre reinforced polymer reinforcement as an alternative to steel reinforcement in concrete is gaining acceptance mainly due to its high corrosion resistance. High strength-to-weight ratio, high stiffness-to-weight ratio and ease of handling and fabrication are added advantages. Other benefits are that they do not influence to magnetic fields and radio frequencies and they are thermally non-conductive. However, the stress-strain relationship for Glass fibre reinforced polymer reinforcement (GFRP) is linear up to rupture when the ultimate strength is reached. Unlike steel reinforcing bars, GFRP rebars do not undergo yield deformation or strain hardening before rupture. Also, GFRP reinforcement possesses a relatively low elastic modulus of elasticity compared with that of steel. As a consequence, for GFRP reinforced sections, larger deflections and crack widths are expected than the ones obtained from equivalent steel reinforced sections for the same load. This investigation provides details of the numerical analysis of GFRP reinforced slabs loaded mechanically using the commercial finite element program (DIANA). To prove the validity of the proposed finite element approach, a comparison is made with experimental test results obtained from full-size slabs. The comparisons are made on the basis of first cracking load, load-deflection response at midspan, cracking patterns, mode of failure and loads at failure. Using the DIANA software for the analysis of GFRP reinforced slabs under mechanical load is possible and can produce acceptable predictions throughout the load range in terms of final load and crack patterns. However, DIANA overestimated the first cracking load and tended to over predict the experimental deflections.